Spices : A survey of the world market (Geneva : ITC Publications, 1982)
Volume 1 of this publication covers significant markets in Europe. chapters typically review supply situation, market characteristics, distribution network, trade practices, promotion and market access factors and give useful addresses.
v.1
eej 18/01/2019
Loans
Keywords: Market Survey